VARIANTS AND PERSPECTIVES OF DRUG REPURPOSING FOR CANCER TREATMENT - A. V. Savinkova; E. M. Zhidkova; L. R. Tilova; M. D. Lavrova; E. S. Lylova; K. A. Kuzin; A. Yu. Portyannikova; V. P. Maximova; A. V. Kholodova; O. A. Vlasova; T. I. Fetisov; K. I. Kirsanov; et al. (Сибирский онкологический журнал, 2018)
Recently many new approaches for repurposing or repositioning of the clinically used drugs have been developed. Drug repurposing  allows not only to use known schemes for the synthesis of  biologically active compounds, but also to avoid multiple studies that  are necessary for drug approval process – analysis of  pharmacokinetics, carcinogenicity, acute and chronic toxicity,  including cardiotoxicity, nephrotoxicity, allergenicity etc. It makes  possible to reduce the number of experimental studies as well as  costs of investigations. In cancer research drug repurposing includes screening for medicines used nowadays for the treatment of patients with non-cancer diseases which possess anticancer activity or able to enhance the effects of the standard anticancer chemotherapy, and  search for new applications of known anticancer drugs for the  treatment of different cancer types. Scientific rationale for the search of the compounds with potential anticancer properties among drugs  with different applications is based on the multiple cross-talks of  signaling pathways, which can inhibit cell proliferation. Modern  advances in genomics, proteomics and bioinformatics, development  of permanently improving databases of drug molecular effects and  high throughput analytical systems allow researchers to analyze  simultaneously a large bulk of existing drugs and specific molecular targets. This review describes the main approaches and  resources currently used for the drug repurposing, as well as a  number of examples.